The gospel according to Shakespeare - Boitani, Piero (University of Notre Dame Press, 2013)
In this book, the author develops his earlier work in The Bible and Its Rewritings, focusing on Shakespeare’s “rescripturing” of the Gospels. The author persuasively urges that Shakespeare read the New Testament with great care and an overall sense of affirmation and participation, and that many of his plays constitute their own original testament, insofar as they translate the good news into human terms. In Hamlet and King Lear, he suggests, Shakespeare’s "New Testament" is merely hinted at, and faith, salvation, and peace are only glimpsed from far away. But in Pericles, Cymbeline, The Winter’s Tale, and The Tempest, the themes of compassion and forgiveness, transcendence, immanence, the role of the deity, resurrection, and epiphany are openly, if often obliquely, staged.